Analytical Method Validation of Thorium in Ore Sample Using UV-Vis Spectrophotometer - Indryati, Suci; Hidayat, Amalia Ekaputri; Pratama, Afiq Azfar; Laksmana, Roza Indra; Widana, Kurnia Setiawan; Ramlan, Muhammad Alif; Purwanti, Tri; Prassanti, Riesna; Anggraini, Mutia; Rommy, Rommy (Badan Riset dan Inovasi Nasional, 2023)
Monazite contains several rare earth elements (REE) along with radioactive elements, i.e., thorium (Th) and uranium (U). Thorium content in monazite is several times higher than uranium. Monazite contains around 12% thorium oxide, but the thorium content in this mineral varies depending on location. To determine the thorium content in monazite, an appropriate and validated analytical method is needed so that the reliability of the test results can be trusted. Apart from that, method validation is one of the clauses in SNI ISO/IEC 17025:2017 that must be fulfilled by the laboratory to be certified and produce reliable data. This research aims to validate analytical methods for non-standard and modified methods that are likely to be used outside the scope. In this research, the method used to digest and analyze thorium in mineral samples refers to the ASTM E2941-14 method with several modifications. Therefore, the analysis method needs to be validated. Validation of the analytical method is carried out by testing several parameters such as linearity and working range tests, accuracy, precision (repeatability), Limit of Detection (LOD), and Limit of Quantitation (LOQ). The results of linearity, accuracy, and repeatability tests that meet the acceptance requirements can be used as a method of validation evaluation. The results of the method validation parameter test met the acceptance requirements, with the linearity test showing a coefficient of determination (R2) of 0.997, the accuracy test showing % a recovery value of 106.22%, and the precision (repeatability) test showing %RSD of 3.76% with LOD value is 0.650 mg/L, and LOQ is 0.724 mg/L. Based on the results of these parameter tests, the method for analyzing thorium in mineral samples was validated.